2022
DOI: 10.1002/advs.202201806
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Formation of Conductive Pathways in Memristive Devices

Abstract: including the URL of the record and the reason for the withdrawal request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The gradual sharpening of the peak could be due to the migration of oxygen vacancies to the grain boundary during recovery stress. [23] In addition to including the recovered domains that were fixed during fatigue, the switching domains also include wake-up domains that did not work under fatigued stress from the beginning. If further recovery stress cycles are applied, domain pinning or dielectric breakdown may occur owing to the stronger stress.…”
Section: Resultsmentioning
confidence: 99%
“…The gradual sharpening of the peak could be due to the migration of oxygen vacancies to the grain boundary during recovery stress. [23] In addition to including the recovered domains that were fixed during fatigue, the switching domains also include wake-up domains that did not work under fatigued stress from the beginning. If further recovery stress cycles are applied, domain pinning or dielectric breakdown may occur owing to the stronger stress.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this particular set of grain boundaries is an ideal precursor for the formation of a conductive filament. 33 The understanding and control of complex defects and their interaction is a key to manipulate conductive filament toward multiple resistive states. While HfO x is one of the mostly used materials in VCM, other materials like Y 2 O 3 with a high amount of intrinsic oxygen vacancies might be even more suited to control the transition between a large number of resistive states.…”
Section: Memristive Behaviors Of Various Materials and Devicesmentioning
confidence: 99%
“…It turns out that the symmetric grain boundary attracts to larger extent oxygen vacancies which, in turn, lead to a higher concentration of electronic states in the band gap of HfO 2 close to the Fermi level. Therefore, this particular set of grain boundaries is an ideal precursor for the formation of a conductive filament . The understanding and control of complex defects and their interaction is a key to manipulate conductive filament toward multiple resistive states.…”
Section: Memristive Behaviors Of Various Materials and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in ref. [150], Winkler et al found that the orientation of the crystal structure in HfO 2 played a significant role in the forming voltage and the memristor's variability. They suggest that the grain boundaries within the HfO 2 control the energy and orientation required to form conductive filaments, and thus proposed controlling the grain boundaries in memristive devices for improved performance.…”
Section: Device Level Issuesmentioning
confidence: 99%